Artificial Intelligence in Music Composition and Production (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The study explores the transformative impact of Artificial Intelligence (AI) on contemporary music composition and production, highlighting its role as a creative and technical collaborator in the modern musical landscape. AI-driven systems such as AIVA, Flow Machines, Jukedeck, Amper Music, and IBM Watson Beat demonstrate the ability of algorithms to generate melodies, harmonies, rhythms, and even lyrics with stylistic coherence and emotional depth. These tools employ machine learning and pattern recognition to analyze vast musical datasets, enabling them to emulate human-like creativity and assist composers in exploring new musical ideas. In production, AI enhances workflow efficiency through automated mastering, mixing, and sound design, allowing for high-quality output with minimal manual intervention. The integration of AI has democratized music creation, making advanced composition tools accessible to both professionals and independent artists. The study concludes that AI does not replace human creativity but amplifies it—bridging artistic intuition and computational intelligence to redefine the boundaries of musical innovation.